A Comprehensive Mini-Review on the Understanding of Electrotherapy for Pain Management: An Introduction to ABMMA-BMT - Mallari, Praveen; Taulier, Tracy; Kamal, Mohammad Amjad (Current Pharmaceutical Biotechnology, 2025)
ABMMA-BMT is a modality that combines innovative complementary and alternative medicine techniques with low-voltage electrical energy, applying it to acupuncture points and meridians to bridge traditional Chinese medicine with modern bioelectric science. This involves the application of microcurrents (10–1000 µA) at acupoints to assess and correct for disrupted energy flow, as determined by electrical resistance measurements. Treatment involves the delivery of weak direct currents, which remove blockages in meridian channels, thereby promoting local blood circulation and tissue repair. Recent research suggests that pulsed electromagnetic fields (PEMFs) and microcurrent stimulation can influence neural signaling, gene expression, and redox balance, thereby benefiting conditions such as chronic pain, soft tissue injury, and functional dysregulation of the immune and endocrine systems. These results suggest that integrating bioelectric principles with traditional acupuncture concepts will support the hypothesis that ABMMA-BMT has the potential to regulate cellular processes and accelerate healing while avoiding invasive procedures. The mechanisms are still not well understood, but preliminary clinical data and experimental studies are good indicators of its therapeutic effect. Future research is needed to standardize treatment parameters and to clinically verify the efficacy of this modality, so that it can be incorporated as a conventional component of healthcare practice.
Keywords: micron stimulation